Conflict management: challenges experienced by nurse-leaders in the hospital environment - Simone Coelho Amestoy; Vânia Marli Schubert Backes; Maira Buss Thofehrn; Jussara Gue Martini; Betina Hörner Schlindwein Meirelles; Letícia de Lima Trindade
This study aimed to understand the main conflicts experienced by nurses-leaders in the hospital environment, as well as the strategies adopted to face them. The study reflects a qualitative descriptive type approach, which was used in the case study as research strategy. The study included 25 nurses who worked in three hospitals in the city of Florianopolis, Santa Catarina. Information where obtained in the months of May to December of 2010 through semi-structured interviews, non-participant observation and dialogical workshops. Data were analyzed using the Thematic Analysis. The results demonstrated the predominant of interpersonal conflicts involving the multidisciplinary team, nurses and the nursing staff. Adopting a participatory leadership, based on dialogue emerges as a strategy for coping with conflicts in the hospital environment.